Identificación y evaluación de riesgos laborales para la elaboración de un manual de trabajo seguro en el laboratorio de veterinaria de Caren de la U.T.C. en el periodo 2016 - Walter Marcelo, Morales Timbila (2017)
Technical management helps to identify, evaluate, control and monitor the risk factors that exist in the veterinary laboratory, as it is one of the four important pillars of the Andean Occupational Safety and Health Instrument Resolution 957, Resolution help.513 of the executive board of the Ecuadorian Social Security Institute. Having performed the diagnosis of the operation and operation of the Veterinary Medicine laboratory in relation to occupational safety and health, identify the unsafe conditions and acts with the potential to cause work accidents by producing a safe work manual with focused preventive measures To the reduction of occupational risks.The present investigation used the descriptive method, that is to say that the information was collected without changing the environment and was based on the collection of information by interviews, and with the help of the "INSHT" matrix that admitted a later analysis of the situation. There is no Safety and Health plan at work in the University, because of the Technical Management Deficit, as expressed by the working community, indicating that they are not very knowledgeable about the subject....